Pengaruh Antara Tingkat Ketegangan Sosial Dengan Tingkat Risiko WBP Melakukan Perilaku Kekerasan Di Rutan Kelas IIB Purworejo - Aditya Bayu Krisna; Mitro Subroto (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2023)
The violent behavior carried out by WBP while he was in prison is a thing that often occurs in prison. Where everyone who enters prison because of criminal cases will definitely experience a lot of pressure from within him or from outside himself. One of the triggering factors is the condition of peison which is over capacity. Violent behavior resulted in disturbances in security and order that disrupted the condition of prison. The purpose of this study was to find out the influence between the level of social tension and the level of risk of WBP committing violent behavior in prison class IIB Purworejo. This type of research is quantitative research. The population in this study is The Correctional Assisted person/prisoner prison class IIB Purworejo in november 2021 with a total of 180 people. The number of samples taken referred to Frankel and Wallen for this type of correlation study, which was as many as 50 respondents. Data collection was carried out by survey using questionnaires distributed to 50 WBP prison class IIB Purworejo as the object of research. Based on data and facts found by researchers at WBP prison class IIB Purworejo that the level of social tension affects the level of WBP risk of violent behavior. The results showed that the level of social tension of WBP Prison class IIB Purworejo was 70.7%. It can be concluded that the level of social tension that exists in the prison environment affects the violent behavior carried out by WBP in prison class IIB Purworejo.